The Influence of Entrepreneurial Mindset and Digital Literacy on Entrepreneurial Decisions Among Generation Z - Saputra, Randi; Fahlia (Al-Qalam Institue, 2025)
This study aims to analyze the influence of entrepreneurial mindset and digital literacy on entrepreneurial decisions among Generation Z in Sumbawa Regency. The study adopts a quantitative approach with a causal-correlational design and involves respondents from Generation Z in Sumbawa and Alas subdistricts, which are centers of active young populations in the region. Data were collected through a structured survey and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the relationships between variables. The results indicate that entrepreneurial mindset has a positive and significant influence on entrepreneurial decision-making among Generation Z, with creativity, innovation, and risk-taking as the primary factors driving entrepreneurial intent. Additionally, digital literacy also has a positive and significant influence, where competence in utilizing digital technology supports the process of identifying opportunities, business innovation, and expanding online marketing networks. Validity and reliability tests of the constructs indicate that the research instrument is highly reliable and internally consistent. The research model shows a high Goodness of Fit (GoF) value, indicating the model's alignment with empirical data. This study emphasizes the importance of strengthening an entrepreneurial mindset and improving digital literacy to build an adaptive, innovative, and highly competitive young entrepreneurial ecosystem in Sumbawa Regency. These findings provide practical contributions to the formulation of digital-based young entrepreneur empowerment strategies at the local level.